Machined Surface Quality in Nano Aluminum Mixed Electrical Discharge Machining - Abdul-Rani, A.M. (Elsevier B.V., 2017)
The development of implants in biomedical engineering application nowadays requires materials with good mechanical and physical properties. Conventional machining of high strength alloy materials is a challenge. Non-conventional machining processes such as electrical discharge machining (EDM) of high strength material have its limitations. Among the limitations are surface modification, induced corrosion, residual stress and reducing of fatigue performance during the EDM process. Nano aluminum mixed electrical discharge machining (PMEDM) is envisaged able to address some of the above mentioned problems. In this study, PMEDM machining performance on biomedical grade titanium alloy workpiece using nano aluminum powder is assessed to establish its improvement for biomedical application. The characteristics analyzed are surface roughness (Ra) and surface morphology. Process variable machining parameters used are peak current, ON-time (pulse duration), gap voltage and nano aluminum concentration. Results of nano aluminum PMEDM on titanium alloy material show slight improvement in terms of surface roughness (Ra) and surface morphology as compared to conventional EDM. PMEDM results show fewer defects in terms of cracks, craters and voids. © 2016